Cuidados de enfermería culturales e integrales en hipertensión arterial. Espacio alternativo del Adulto Mayor. Santiago. periodo diciembre 2022 – abril 2023. - Gómez Zavala, Nelly Margarita (2023)
The prevalence of arterial hypertension (AHT) is constantly increasing throughout the world, it is attributed to multiple causes, one of them being arterial stiffness as a consequence of the aging of the population, cultural and comprehensive nursing care in the elderly are essential for provide appropriate and person-centred care. Recognizing and respecting the cultural diversity of older adults, along with addressing their physical, emotional, social, and spiritual needs, is essential to provide them with quality care and promote their comprehensive well-being. Integral in arterial hypertension. Alternative space for the elderly. Santiago. Period December 2022 - April 2023" with the objective of delimiting the most appropriate cultural and comprehensive nursing care for elderly patients with arterial hypertension in the Alternative Space for the elderly. Santiago. period December 2022 - April 2023, the level of the research was descriptive, bibliographical and field with a quantitative, cross-sectional approach due to the time spent for data collection, where a questionnaire was used that was validated by three experts, with a population of 10 professionals responsible for providing care to older adults with arterial hypertension, based on these results it is concluded that professionals always investigate the qualities of patients for which they provide care where the culture, beliefs and characteristics of each individual are taken into account. Keywords: hypertension arterial, nursing care, cultural, comprehensive, older adults-